Kilka przykładów niestandardowych rozwiązań zadań z rachunku prawdopodobieństwa - Dniestrzański, Piotr; Sacała, Jerzy (Some Non-Standard Examples of Tasks Solution of Probability Calculus, 2006)
The authors present and analyse atypical solutions concerning probability calculus in secondary schools and basic course at economic universities. They also mention their influence on understanding of discussed problems by students of different types of schools.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 26-32